2011
DOI: 10.1523/jneurosci.2482-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Noisy Neurons to Coincident Inputs

Abstract: How do neurons compute? Two main theories compete: neurons could temporally integrate noisy inputs (rate-based theories) or they could detect coincident input spikes (spike timing-based theories). Correlations at fine timescales have been observed in many areas of the nervous system, but they might have a minor impact. To address this issue, we used a probabilistic approach to quantify the impact of coincidences on neuronal response in the presence of fluctuating synaptic activity. We found that when excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 54 publications
(69 reference statements)
0
43
0
Order By: Relevance
“…The oscillations entrain rhythmic neural firing in the thalamus and, subsequently, in the forebrain that synchronize with the midbrain oscillations. The thalamic oscillations enable more effective communication between the thalamus and forebrain first, by creating temporally aligned windows of excitability between the thalamus and forebrain [64]; and second, by enhancing transmission efficacy by coincidence-dependent temporal integration, that is, coincident spikes are more effective at driving post-synaptic targets than incoherent spikes [65,66] (Figure 3a, top versus bottom).…”
Section: Discussionmentioning
confidence: 99%
“…The oscillations entrain rhythmic neural firing in the thalamus and, subsequently, in the forebrain that synchronize with the midbrain oscillations. The thalamic oscillations enable more effective communication between the thalamus and forebrain first, by creating temporally aligned windows of excitability between the thalamus and forebrain [64]; and second, by enhancing transmission efficacy by coincidence-dependent temporal integration, that is, coincident spikes are more effective at driving post-synaptic targets than incoherent spikes [65,66] (Figure 3a, top versus bottom).…”
Section: Discussionmentioning
confidence: 99%
“…Both these features have been observed in a wide range of different cell types. It seems likely that fluctuation-driven spiking and the concomitant increase in membrane conductance associated with synaptic inputs are general features of mammalian central neurons during active states (Rossant et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that nerve cells can be extremely sensitive to synchronous input from large groups of neurons [30], More precisely, a neuron's firing rate profile depends, to a large degree, on higher-order correlations among the presynaptic spikes [31], Of course, which synchronous patterns are favored by the network is also determined hy its connection structure. While the contribution of specific structural motifs to the emergence of pairwise correlations (i.e., two-spike patterns) has already been dissected [16], no such result exists in the case of more complex patterns, stemming from correlations of higher order.…”
Section: Introductionmentioning
confidence: 99%